Financial Infidelity in Couple Relationships - Michelle Jeanfreau; Kenji Noguchi; Michael D. Mong; Hans Stadthagen (Journal of Financial Therapy, 2018)
Four hundred and fourteen participants answered questions regarding financial habits within the context of the couple relationship. The Big Five Personality Inventory and a Martial and Life Satisfaction Scale were used to determine the incidence and factors associated with financial infidelity. Results indicated that 27% of participants have kept a financial secret from their partner. Furthermore, both marital and life satisfaction were lower for participants who have experienced financial infidelity than in those who have not. Finally, conscientiousness, a factor from the Big Five Personality Inventory, showed a significant difference, suggesting that more organized individuals were less likely to keep financial secrets. Clinical implications are also discussed.
Keywords: Couples; Finances; Relationships; Infidelity